Multicenter real‐world data of patients harboring rare mutations other than EGFR or ALK in advanced or metastatic non‐small cell lung cancer. Issue 3 (8th December 2021) - Lee, Su Yeon; Kim, Young Chul; Lee, Kye Young; Lee, Sung Yong; Lee, Shin Yup; Lee, Min Ki; Lee, Jeong Eun; Jang, Seung Hun; Jang, Tae‐Won; Choi, Chang Min
Abstract: Background: Studies on the application of targeted therapies for patients with non‐small cell lung cancer (NSCLC) who harbor rare genetic mutations are ongoing. In the present study, we investigated the real‐world data of NSCLC patients who harbor rare mutations. Methods: We retrospectively analyzed patients with advanced or metastatic nonsquamous NSCLC aged >20 years with confirmed rare mutations ( BRAF, ROS1, MET, RET, HER2, FGFR, and NTRK ) from January 2015 to September 2020 at nine tertiary hospitals. In addition, we validated the lung cancer PCR panel kit in patients with confirmed mutations by NGS. Results: Among 118 patients included, 88 received platinum‐based chemotherapy as first‐line chemotherapy. The progression‐free survival of patients with BRAF, ERBB2, MET, RET, and ROS1 mutations was 10.9 months (95% confidence interval [CI]: 1.3–20.5), 5.3 months (95% CI: 3.0–7.5), 7.2 months (95% CI: 3.6–10.9), 11.4 months (95% CI: 9.2–13.6), and 10.0 months (95% CI: 3.7–16.4) respectively ( p  = 0.041). The median overall survival (OS) was not reached in patients with ROS1 mutations; however, in BRAF, ERBB2, MET, and RET mutant patients, median OS was 14.1 months (95% CI: 10.1–14.1), 34.5 months (95% CI: 13.2–36.9), 22.7 months (95% CI: 1.7–24.0), and 29.8 months (95% CI: 28.9–61.3), respectively ( p  = 0.006). Of the 27 tissue samples, 26 (96.3%) showed the same PCR panel kit result with NGS. Conclusions: First‐line platinum‐based chemotherapy showed durable benefit in patients with advanced or metastatic nonsquamous NSCLC harboring rare genetic mutation other than EGFR or ALK. Abstract : This study shows real‐world data of NSCLC patients with rare genetic mutations, and the majority of patients were treated primarily with platinum‐based chemotherapy. First‐line platinum‐based chemotherapy showed durable benefit in patients with advanced or metastatic nonsquamous NSCLC harboring rare genetic mutations other than EGFR or ALK.